What matters and who matters to young people leaving care: a new approach to planning: by Peter Appleton, Bristol, Policy Press, 2024, 191 pp., ISBN 9781447368335 (pb), ISBN 9781447368359 (eBook), £ 16.99 (pb), £ 0.00 (Open Access via Bristol University Press Digital) - Williamson, Howard (European Journal of Social Work, 2025)
The article discusses the challenges faced by young people leaving public care systems, emphasizing the need for a re-evaluation of support strategies. It highlights the concept of "compounded adversity," which affects their educational and employment outcomes, mental health, and overall life prospects. The author advocates for a new planning approach that prioritizes the perspectives and needs of care-experienced individuals, drawing on a model that incorporates their values around relationships and personal time. Despite some critiques regarding the book's structure and repetitiveness, it contributes significantly to the discourse on improving support for these young people as they transition to independence.